2001
DOI: 10.1523/jneurosci.21-07-02278.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilaments Are Nonessential to the Pathogenesis of Toxicant-Induced Axonal Degeneration

Abstract: Axonal neurofilament (NF) accumulations occur before development of symptoms and before other pathological changes among idiopathic neurodegenerative diseases and toxic neuropathies, suggesting a cause-effect relationship. The dependence of symptoms and axonal degeneration on neurofilament accumulation has been tested here in a transgenic mouse model (Eyer and Peterson, 1994) lacking axonal NFs and using two prototypic toxicant models. Chronic acrylamide (ACR) or 2,5-hexanedione exposure resulted in progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 45 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…The neurotoxic action of AA was suggested to be due to effects on cells of the central and peripheral nervous system including changes in cellular metabolism (Howland et al, 1980;Brimijoin and Hammond,1985;Medrano and LoPachin, 1989;Exon, 2006), changes in gene transcription and protein synthesis (Cavanagh and Nolan, 1982a,b;Cavanagh, 1982;Cavanagh and Gysbers, 1983;Bisby and Redshaw, 1987;Lin et al, 2000;El-Alfy et al, 2011;Seale et al, 2012), effects on neurotransmitter levels and turn-over (Dixit et al, 1981;Uphouse and Russell, 1981;Aldous et al, 1983;Shi et al, 2012), binding to cellular proteins including damage to microtubular and neurofilamental proteins (Hashimoto and Aldridge, 1970;Tanii and Hashimoto, 1983;Carrington et al, 1991;Reagan et al, 1994;Abou-Donia, 1996, 1997;Lapadula et al, 1989;Xiwen et al, 1992), changes in ion distribution (Lehning et al, 1998;LoPachin and Lehning, 1994), and axonal transport (Chretien et al, 1981;Miller and Spencer, 1984;Gold et al, 1985;Moretto and Sabri, 1988;Logan and McLean, 1988;Harry et al, 1989;Sabri and Spencer, 1990;Martenson et al, 1995;Sickles et al, 1995Sickles et al, ,1996Stone et al, 2001). However, the minimal effects of AA-treatment, by up to a maximally tolerated dose, on: (i) gene expression related to cholinergic, noradrenergic, dopaminergic, GABAergic, or glutamatergic neurotransmitter systems; (ii) neurotransmitter levels related ...…”
Section: Mode Of Action Of Neurotoxicitymentioning
confidence: 99%
“…The neurotoxic action of AA was suggested to be due to effects on cells of the central and peripheral nervous system including changes in cellular metabolism (Howland et al, 1980;Brimijoin and Hammond,1985;Medrano and LoPachin, 1989;Exon, 2006), changes in gene transcription and protein synthesis (Cavanagh and Nolan, 1982a,b;Cavanagh, 1982;Cavanagh and Gysbers, 1983;Bisby and Redshaw, 1987;Lin et al, 2000;El-Alfy et al, 2011;Seale et al, 2012), effects on neurotransmitter levels and turn-over (Dixit et al, 1981;Uphouse and Russell, 1981;Aldous et al, 1983;Shi et al, 2012), binding to cellular proteins including damage to microtubular and neurofilamental proteins (Hashimoto and Aldridge, 1970;Tanii and Hashimoto, 1983;Carrington et al, 1991;Reagan et al, 1994;Abou-Donia, 1996, 1997;Lapadula et al, 1989;Xiwen et al, 1992), changes in ion distribution (Lehning et al, 1998;LoPachin and Lehning, 1994), and axonal transport (Chretien et al, 1981;Miller and Spencer, 1984;Gold et al, 1985;Moretto and Sabri, 1988;Logan and McLean, 1988;Harry et al, 1989;Sabri and Spencer, 1990;Martenson et al, 1995;Sickles et al, 1995Sickles et al, ,1996Stone et al, 2001). However, the minimal effects of AA-treatment, by up to a maximally tolerated dose, on: (i) gene expression related to cholinergic, noradrenergic, dopaminergic, GABAergic, or glutamatergic neurotransmitter systems; (ii) neurotransmitter levels related ...…”
Section: Mode Of Action Of Neurotoxicitymentioning
confidence: 99%
“…The administration of acrylamide also increases the expression of mRNA for NF proteins and the phosphorylation of NF in rats [444][445][446] but decreases their degradation [447]. However, acrylamide-induced neurotoxicity is not initiated exclusively through its action on axonal NF because NF-deficient mutant quiver quails, crayfish (a species lacking NF) and NFH-LacZ mice are sensitive to neurotoxic effects of acrylamide [448][449][450].…”
Section: Toxic Agents That Disorganise the Neurofilament Networkmentioning
confidence: 99%
“…ACR toxicity results in the accumulation of NFs, swelling of distal axons, increase in tubulovesicular bodies and progressive senorimotor impairment (Prineas, 1969;Spencer and Schaumburg, 1974). However, ACR causes similar behavioral impairment, axonal pathology and transport defects in mice genetically lacking NFs, suggesting that disruption of NFs is not required for ACR-mediated toxicity (Stone et al, 2001). Evidence suggesting that ACR-mediated toxicity acts specifically at the synapse comes from a study which observed terminal degeneration and behavioral deficits in the absence of any degenerative changes in the axon (Lehning et al, 2003).…”
Section: Cmt1mentioning
confidence: 99%